KUALITAS PELAYANAN MASYARAKAT DILIHAT DARI ASPEK TANGIBLE (BERWUJUD) PADA PUSKESMAS TANTA KECAMATAN TANTA KABUPATEN TABALONG - Syahrani Syahrani (Jurnal PubBis, 2019)
The purpose of this study is to find out and analyze how the Quality of Service in Tanta Health Center is to create good service for the community. In this case to find out the Service Quality that is given to the community, the researcher only focuses on one indicator, namely on the Tangible aspect. The research method used is descriptive-quantitative. This study uses questionnaire techniques or questionnaires that are giving to 30 respondents who are considered to have knowledge in research. Data collection techniques used are questionnaire or questionnaire. The data analysis technique using frequency distribution tabulation. The results showed that the Quality of Community Services seen from the Tangible (Tangible) aspect of the Tanta Community Health Center, Tanta District, Tabalong Regency can be categorized as "quite high quality". Keywords: General Poly, Service Quality, Quality Service